Experimental investigation and empirical model to determine the damping and shear stiffness properties of soft rock under multistage cyclic loading. Issue 147 (August 2021) - He, M.M.; Zhang, Z.Q.; Li, N.
Abstract: The damping and shear stiffness properties of soft rock play important roles in the stability of rock masses in earthquake-prone regions. The shear modulus and damping ratio are two important dynamic rock parameters that can significantly impact the results of a seismic response analysis. Cyclic loading tests were carried out on sandstone, conglomerate and glutenite specimens at different stress levels, stress amplitudes, confining pressures and moisture contents to investigate the damping behaviour of soft rock. The effects of the stress amplitude, strain amplitude and stress level on the shear modulus and damping parameters were investigated, and the damping behaviour was comparatively analysed under different loading conditions. The dynamic shear modulus was correlated with the stress amplitude of soft rock. The results showed that as the stress amplitude decreased, the moisture content had less of an effect on the dynamic shear modulus and more of an effect on the damping parameters. The damping parameters under cyclic loading were larger for multistage stress levels than for multistage stress amplitudes. The hyperbolic model was used to describe the stress-strain relationship of soft rock under multistage cyclic loading. Finally, an empirical model was proposed to correlate the dynamic shear modulus with the damping ratio of soft rock at different stress levels and stress amplitudes and was found to effectively describe the damping behaviour of soft rock under multistage cyclic loading. Highlights: Cyclic loading tests were carried out on soft rocks to investigate the damping behaviour of soft rock. The effects of the stress level, confining pressure and moisture content on the damping parameters were investigated. An empirical model was proposed to correlate the dynamic shear modulus with the damping ratio of soft rocks.